Dossiê Interfaces da Filosofia Africana - Machado, Adilbênia Freire; Dantas, Luís Thiago Freire; Corrêa, Rogério Saucedo; Noguera, Renato (Voluntas: Revista Internacional de Filosofia, 2019)
O trabalho não apresenta resumo.